PENGETAHUAN MASYARAKAT TENTANG BARANG ELEKTRONIK BEKAS (E WASTE) DI KOTA SEMARANG - Anief Rufiyanto; Widi Astuti (Universitas Pandanaran, 2017)
Indonesian is one of the largest consumers of home electronics in Asia. It is thereforeconceivable that in the next few years Indonesian will experience E-Waste booming. Thisdoes not include the amount of E-Waste entering Indonesian illegally from somedeveloped countries. From the results of a preliminary survey conducted by the BCRCSEA Jakarta in 2007, compared to other developing countries in Southeast Asia, peopleawareness towards the problems of E-Waste in Indonesian is relatively left behind. Thisstudy attempts to analyze public perceptions and behavior towards waste and the factorsthat influence waste management in Semarang. This study also tries to find out how muchthe public’s willingness to engage in recycling electronic waste. The findings showed thatpublic perception in Semarang toward E-Waste and its recycling considered low. Whilemost of respondents preferred to get service and reparation for their out of orderelectronics. Respondents argued that E-Waste recycling will merely benefit certainparties. It also due to respondents’ low knowledge on E-Waste and its recycling. Mostrespondents, however, stated that they were ready to participate in recycling E-Waste,with expenditure around Rp5,000,- up to Rp10,000,-. From the study results, demograficvariable influenced respondents’ perception and behavior, though it was insignificant.Whereas factors that shaped and influenced public’s willingness in Kota Semarang to beinvolved in E-Waste recycling was respondent’s assessment concerned to currentenvironmental condition, public perception and behavior toward E-Waste dan itsrecycling effort, the cost in carrying out E-Waste recycle process, and their knowledgeabout E-Waste and its recycle possibility.Key Word : E-Waste, recycle, perception and behavior, willingnes